The politics of the new welfare state - Bonoli, Giuliano; Natali, David (Oxford : Oxford University Press, 2012)
In this title, the main reforms in work and welfare are summarised and analysed to provide evidence of policy change and its main determinants to policymakers, researchers, and stakeholders interested in the field.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Welfare state -- European Union countries; European Union countries -- Politics and government